1998
DOI: 10.1152/ajpendo.1998.275.5.e757
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid-independent inhibition of tumor necrosis factor production by the neuropeptide urocortin

Abstract: Urocortin (UCN) is a neuropeptide homologous with corticotropin-releasing factor (CRF), which has anti-inflammatory activities not all mediated by corticosteroids. In mice, UCN (1 μg/mouse sc) significantly reduced lipopolysaccharide (LPS)-induced serum tumor necrosis factor (TNF) and interleukin (IL)-1β levels in vivo but did not affect serum IL-6. These effects were paralleled by a rise in corticosterone (CS) levels. Blockade of the CS increase by cyanoketone did not prevent TNF inhibition by UCN, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
1
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 30 publications
2
51
1
5
Order By: Relevance
“…In vitro, Ucn and UcnII mediate anti-inflammatory effects by causing macrophage apoptosis (15) and stimulate the production of IL-6, which has immunomodulatory effects, in aortic smooth muscle cells (16), via CRHR2 activation. In vivo, Ucn suppresses experimental autoimmune encephalomyelitis in rats (17), reduces LPS-induced serum TNF␣ and IL-1␤ levels in mice (18), and decreases mortality after cecal ligation and puncture or following injection with bacterial endotoxin (19). However, the interpretation of those studies might be complicated by the fact that Ucn can directly up-regulate glucocortocoid production, which has anti-inflammatory effects (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, Ucn and UcnII mediate anti-inflammatory effects by causing macrophage apoptosis (15) and stimulate the production of IL-6, which has immunomodulatory effects, in aortic smooth muscle cells (16), via CRHR2 activation. In vivo, Ucn suppresses experimental autoimmune encephalomyelitis in rats (17), reduces LPS-induced serum TNF␣ and IL-1␤ levels in mice (18), and decreases mortality after cecal ligation and puncture or following injection with bacterial endotoxin (19). However, the interpretation of those studies might be complicated by the fact that Ucn can directly up-regulate glucocortocoid production, which has anti-inflammatory effects (17,18).…”
mentioning
confidence: 99%
“…In vivo, Ucn suppresses experimental autoimmune encephalomyelitis in rats (17), reduces LPS-induced serum TNF␣ and IL-1␤ levels in mice (18), and decreases mortality after cecal ligation and puncture or following injection with bacterial endotoxin (19). However, the interpretation of those studies might be complicated by the fact that Ucn can directly up-regulate glucocortocoid production, which has anti-inflammatory effects (17,18). On the other hand, UcnII treatment worsens Listeria monocytogenes infection in mice via up-regulation of .…”
mentioning
confidence: 99%
“…The mechanism of stimulating the secretion of Ucn-2 hormone in early HF is not clear. The previous studies indicated that an activated serum Ucn hormones were related to antiinflammatory response (reducing the interleukin and tumor necrotizing factor secretion), in exaggerated hyperadrenergic state, or as a cardioprotective role of Ucn (Ucn-1, Ucn-2 isoforms and Ucn) in HF process (12,13,27,28). The reason for the lack of the serum Ucn-2 response in the presence of moderate to severe left ventricular dysfunction (Group A) may be due to withdrawal of anti-inflammatory and cardioprotective response in HF process.…”
Section: Discussionmentioning
confidence: 99%
“…While urocortin reduces serum TNF-α and IL-1B levels, it increases IL-6 secretion. Urocortin is a potent mediator in mast cell degranulation and increases vascular permeability [9].…”
mentioning
confidence: 99%